2022
DOI: 10.1021/acsmedchemlett.2c00149
|View full text |Cite
|
Sign up to set email alerts
|

Novel Isoindolinone-Based Analogs of the Natural Cyclic Peptide Fenestin A: Synthesis and Antitumor Activity

Abstract: Small-and medium-sized cyclopeptides have been found to have extensive bioactivities and have drawn much attention from medicinal chemists. In the work described in this paper, various cyclic peptide analogs of Fenestin A were synthesized by intramolecular photoinduced electron-transfer cyclization reactions to study the influence of slight structural changes on the bioactivity of small cyclopeptides. The incorporation of thiazole and rigid isoindolinone fragments was found to improve the bioactivity of the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Furthermore, these results are in consonance with earlier reports that mentioned isoindolinone derivatives majorly as regulators of Cyclins and CDKs and modulator of PI3K-Akt-dependent G1 arrest. 21 , 37 , 38 This could be probed further to evaluate Cyclins and CDKs as the molecular targets of these 3-methyleneisoindolinones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these results are in consonance with earlier reports that mentioned isoindolinone derivatives majorly as regulators of Cyclins and CDKs and modulator of PI3K-Akt-dependent G1 arrest. 21 , 37 , 38 This could be probed further to evaluate Cyclins and CDKs as the molecular targets of these 3-methyleneisoindolinones.…”
Section: Resultsmentioning
confidence: 99%
“…In silico ADME profiling of representative compounds revealed their drug-likeness properties, and the synthesized compounds fulfill the criteria to be a drug candidate. Further, earlier reports have mentioned isoindolinone derivatives as inhibitors of MDM2-p53 interactions, regulators of Cyclins and CDKs, inhibitors of PARP-1, and modulator of PI3K-Akt-dependent G1 arrest. ,,,, The role of tumor suppressor p53 in regulation of cell cycle and apoptosis is well known, and MDM2-p53 axes have been reported to be involved in onsets of HNSCC. Additionally, Tp53 mutation is one of the most frequent genetic alterations in head and neck squamous cell carcinoma (HNSCC) and results in an accumulation of p53 protein in tumor cells. This makes the MDM2-p53 axis an attractive target point to improve HNSCC therapy by modulation of tumor suppression activities and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our team focused on the structural modification of various a Key Laboratory for Photonic and Electronic Bandgap Materials (Ministry of natural peptides by IPETC reactions to develop novel antitumor agents. [11][12][13] We found that many of the compounds with an isoindolinone moiety showed good antitumor activitiy. We have also observed that the IPETC synthesis of cyclic peptides starting from chiral pure amino acids can generate chiral pure products (mainly the C-3 chiral center), since the chiral starting material may significantly affect the spatial properties of the precursor in the cyclization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 The structural modification of natural cyclic peptides phakellistatin 2, phakellistatin 6 and fenestin A also showed that the compounds with the same amino acid sequence yet different spatial structural features presented disparate antitumor activities. 11,13,15 It has been reported that introduction of methylated Pro residues into the peptide would increase the percentage of the cis conformation of Pro and rescue the biological activity from synthetic cyclopeptides. 16 Therefore, we here attempt to investigate the effect of chiral amino acids on the chiral character of C-3 in isoindolinone and on the bioactivity.…”
Section: Introductionmentioning
confidence: 99%